Scarcity of Subsidized Fertilizer in South Tapanuli Regency - Safran Efendi Pasaribu; Oman Sukmana; Wahyudi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The scarcity of subsidized fertilizer supplies in South Tapanuli Regency makes the economy increasingly difficult for farmers. The aim of this research is to find out the causes of the scarcity of subsidized fertilizer, the impact felt by farmers, and the efforts or strategies of farmers amidst the scarcity of subsidized fertilizer. The research method uses a qualitative descriptive approach, with data from observations, interviews and literature studies. The research results show that most farmers know that the scarcity of subsidized fertilizer is not caused by a lack of stock from the government. However, there were several unscrupulous employees and distributors who diverted the subsidized fertilizer to be resold to other farmers at different prices. The impact felt by farmers due to the scarcity of fertilizer is a decrease in the quality of the harvest, low selling prices for grain, and a decrease in income that is not balanced with high expenditure. The strategy or effort made by farmers is to buy non-subsidized fertilizer, although in limited quantities. Farmers hope that the government can curb these 'naughty' employees and distributors so that stocks and prices return to normal so they can help ease the farmers' economy.